Corpus Alienum Esofagus berupa Gigi Palsu pada Pria Dewasa: Laporan Kasus - Umniya; Mukhlis Imanto (Medula, 2026)
Esophageal foreign body is a medical emergency frequently encountered in ENT-Head and Neck Surgery clinical practice. This condition requires an accurate diagnosis and prompt management to prevent serious complications, such as esophageal perforation, mediastinitis, and even death. Dentures are a type of foreign body with a high risk of causing esophageal impaction due to their irregular shape, relatively large size, and often containing wires or sharp edges that can damage the gastrointestinal mucosa. This case report discusses a 46-year-old man with a chief complaint of a lump in his throat accompanied by pain when swallowing. These symptoms occurred after the patient woke up and realized his dentures were missing. Plain anteroposterior and lateral radiographs of the neck revealed a radiopaque foreign body shadow in the esophageal projection located at the level of the 7th cervical to 1st thoracic vertebrae (C7–T1). Based on these clinical and radiological findings, the patient was immediately scheduled for a rigid esophagoscopy under general anesthesia. Careful extraction of the foreign body using alligator forceps was successful, resulting in the intact removal of the broken piece of denture plate. Post-operatively, a thorough evaluation revealed no mucosal tears or other complications, either during or after the interventional procedure. This case demonstrates that a thorough history, accurate radiological examination, and prompt esophagoscopy are crucial in reducing morbidity in patients with esophageal foreign bodies.